The Effect of Educational Intervention on Promoting Healthy Eating Behaviors among Primary School Students in Kermanshah City, Iran - Somayeh Ebrahimi; Fazlollah Ghofranipour; Mahmoud Tavousi (Journal of Education and Community Health)
Background and Objectives: Nutrition is important during childhood for growth and to help prevent infections and other diseases and educational interventions will be effective. The aim of this study was to examine the effect of educational intervention on promoting healthy eating behaviors among primary school students of Kermanshah City, Iran. Materials and Methods: In this semi-experimental study, 135 primary school students were randomly allocated into intervention and control groups. Data were collected using a valid and reliable questionnaire before and after the intervention in the areas of knowledge, attitude, practice and demographic variables. Data were analyzed using Chi-square, and paired t test with the SPSS-13 software. Results: Results showed that after the educational intervention the mean scores of knowledge, attitudes and practice were increased significantly in the experimental group (P<0.001), but not in the control group (P>0.05). Conclusions: The results of this study showed that the educational intervention was effective in creating positive changes in knowledge, attitude and especially behaviors of the students about healthy eating. According to the appropriate education in schools and low-cost and effective nutritional education, the need to extend this type of training programs seems necessary.